Pharmacokinetics of Linezolid and Ertapenem in experimental parapneumonic pleural effusion - Saroglou, Maria (BioMed Central, 2010)
OBJECTIVE: To determine the extent of linezolid and ertapenem penetration into the empyemic fluid using a rabbit model of empyema. METHODS: An empyema was created via the intrapleural injection of Escherichia coli bacteria (ATCC 35218) into the pleural space of New Zealand white rabbits. After an empyema was verified by thoracocentesis, 24 hours post inoculation, linezolid (10 mg/kg) and ertapenem (60 mg/kg) were administered intravenously into 10 and 8 infected empyemic rabbits, respectively. Antibiotic levels were determined in samples of pleural fluid and blood serum, collected serially at 1, 2, 4, 6 and 8 hours, after administration each of the two antibiotics. RESULTS: Linezolid as well as ertapenem penetrate well into the empyemic pleural fluid, exhibiting a slower onset and decline compared to the corresponding blood serum levels. Equilibration between blood serum and pleural fluid compartments seems to occur at 1.5 hours for both linezolid and ertapenem, with peak pleural fluid levels (Cmax(pf )of 2.02 ± 0.73 «mu»g/ml and Cmax(pf )of 3.74 ± 1.39 «mu»g/ml, correspondingly) occurring 2 hours post antibiotics administration and decreasing very slowly thereafter. The serum concentrations for both antibiotics were significantly lower from the corresponding pleural fluid ones during the 8 hours collecting data, with the exception of samples collected at the 1(st )hour (Cmax(serum )of 2.1 ± 1.2 «mu»g/ml for linezolid and Cmax(serum )of 6.26 ± 2.98 «mu»g/ml for ertapenem). CONCLUSION: Pleural fluid levels of both antibiotics are inhibitory for common specified pathogens causing empyema.